Relevance of Specific Surface of Mixed Oxide Derived from Layered Double Hydroxides on the Rheological Properties and Porosity of Cement Pastes - C. dos Santos, Caio [UNESP]; Almeida, Adriana A. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP] (American Chemical Society (ACS), 2025)
Cement-based products are the synthetic materials most used by humans, with consequent environmental impacts. One strategy that can assist in mitigating the adverse environmental effects of these materials involves the incorporation of multifunctional nanostructured additives. The objective of this work was to demonstrate the efficacy of incorporating mixed oxides (MO) derived from layered double hydroxides (LDH) to control the rheology and porosity of cement-based matrices. Thermal aging of LDH enabled the preparation of MO with different specific surface areas (SSA) for incorporation in different amounts in Portland cement. A low proportion of MO and low SSA increased workability by 22%. In contrast, a high proportion of MO and high SSA led to a 2.4-fold acceleration of cement consolidation and a 36.9% decrease of the porosity of the composite. These features could be attributed to additive-matrix interactions, with the LDH memory effect playing key roles in the cement crystal seed process and in competition for the absorption of free water within the cement paste. Therefore, the unprecedent results obtained suggest that the quantity and SSA of MO are key parameters to fine-tune the paste rheology and structure of hidrated cement. The MO materials showed easy adaptability and excellent potential for use as multifunctional additives in the production of eco-friendly, high-performance cement paste formulations with controllable properties according to the desired application.
Keywords: Cement-based products; LDH; Memory effect; Porosity control; Portland cement; Rheology control